The Impact of Piriformospora indica on plant heat and drought tolerance - Ji, Hao; Zhang, Min; Huang, Chuanhuang; Lin, Wei; Lu, Yin; Wang, Peijie; Dong, Bin; He, Bizhu; Wu, Binghua; Guo, Lijin (Frontiers in Plant Science, 2024)
In recent years, the global rise in temperatures has led to drought and heat becoming major environmental stresses that limit plant growth. Previous research has demonstrated the potential of Piriformospora indica in augmenting plant stress resistance. However, specific studies on its effects and underlying mechanisms in cuttings of Rosa chinensis, Jasminum sambac, and Rhododendron simsii Planch are relatively limited. The objective of this study is to explore the effects and mechanisms of P. indica on cuttings and tissue-cultured seedlings of these plants under conditions of drought and high-temperature stress. The experiment involved subjecting P. indica-inoculated and non-inoculated plants to drought (one week without watering) and high-temperature (24-hour exposure to 45℃) stress in a controlled environment chamber. Indicators such as chlorophyll content, chlorophyll fluorescence parameter Fv/Fm, and antioxidant enzyme activity were measured. The results showed that inoculation with P. indica significantly increased the survival rate of the three types of plant cuttings under drought conditions by 13%, 17%, and 16.6% respectively, and resulted in a substantial decrease in malondialdehyde content alongside an increase in chlorophyll content. Under high-temperature stress at 45℃, the chlorophyll fluorescence parameter Fv/Fm values increased by 27.3%, 10.3%, and 51.1% compared to the control group. Furthermore, heat tolerance tests at 42℃ showed a 2% higher survival rate in the P. indica inoculated Rhododendron tissue-cultured seedlings than in the control group, with a positive effect observed on the activities of superoxide dismutase and peroxidase. These findings demonstrate that inoculation with P. indica significantly enhances the resistance of Rhododendron, Jasminum sambac, and Rosa to drought and high-temperature stresses, providing insights for sustainable agricultural development and the comprehensive exploitation of the potential value of P.indica.